The Development of Curriculum School Model Based on the Internet of Things - ., Subagyo; Eko Siswoyo, Rasdi; ., Soesanto; Rachman, Maman; Nurdiyanto, Heri (International Journal of Engineering and Technology, 2018)
The background of this study is based on field conditions that Tamansiswa schools established since Indonesia have not been independent until now there has been no progress, even from schools that ever exist today many are closed due to lack of students. This research is classified in research and development, where researchers interpret the mindset and behavior of research subjects in carrying out the work. As the subject of the investigation is the principal in carrying out the work so far. The research was conducted at Vocational High School. The purpose of the study to describe the implementation of Vocational Middle School curriculum internet of things during this time, then, developed based on the internet of things theory and principles into the final model. Data collection using interviews, observation, and documentation. Data analysis is based on the qualitative descriptive study. The results showed that in the middle school Vocational Education did not implement the principles of the internet of things consisting of planning, implementation, and evaluation as a whole. The vision of the mission has not yet described the achievement of the targets, and the curriculum internet of things has not followed the accomplishments of the goals made before and is spontaneous, the evaluation of the implementation is not followed up and finished without any documents that can be used to reflect something done. This study concludes that the planning, implementation, and evaluation of curriculum internet of things industry 4.0 has not been optimal. The results of this study can be used as a reference for the implementation of curriculum based on the principles of the appropriate internet of things, a clear plan, and implemented realistically, and the existence of reflection and evaluation.Â Â